Career Support dalam Peran Mentoring Kepala Ruangan terhadap Keselamatan Pasien Rawat Inap di Rumah Sakit Medika Lestari - Susanthy, Adhita; Adhikara, M.F. Arrozi; Indrawati, Ratna (Journal of Hospital Management, 2020)
Patient safety with clinical governance and efficiency were important in ensuring the quality of health services. Based on the incidence report, data on the incidence of falling patients, medication errors, and patient identification errors were obtained. Where all of these incidents occurred in the inpatient room. The purpose of this study will prove the influence of the mentoring function on the safety of inpatients in Medika Lestari hospital. This research is an explanatory causality research with a quantitative approach in the form of hypothesis testing, and taking research data at a certain time (cross sectional). Samples were obtained by sampling saturated with a population of 30 people. Data collection was done by survey. Data analysis was performed by multiple linear regression. The results of this study indicates the positive influence of career support, psychosocial support, and role modeling factors from the head of inpatient room together on patient safety, significantly positive influence of career support factors on patient safety, significantly positive influence of psychosocial support factors on patient safety, and the significant negative effect of role modeling on patient safety. The findings of this study indicates that the most influential variable on the safety of inpatients at Medika Lestari Hospital is the career support variable from the head of inpatient the room. Based on this research it is recommended that hospital is going to provide career support to employees to improve patient safety by providing incentives, promotions, and funding for seminars or training.Keywords: patient safety, head room mentoring, career support, psychosocial support, and role modeling